Islamic Integrated Cognitive Behavioral Therapy for Treating Depression in Young Adults: A Quasi- Experimental Study - Binish Nawaz; Tahira Yousuf (Proceedings)
Introduction: Integrating Islamic principles along with the traditional Cognitive Behavioral Therapy (CBT) is used to help reduce the symptoms of depression in young adults. Islamic integrated cognitive Behavioral Therapy (IICBT) helps boosting spiritual feelings of the patients which have the potential to reduce depressive symptoms.